Decreasing Preoperative Autologous Blood Donation: Collaboration Between a Hospital and a Blood Center to Prompt Change in Physician Ordering Behavior. Issue 1 (29th August 2015) - Su, Leon L.; Adamski, Jill; Gilman, Elizabeth A.; Cusick, Robin; Hernandez, James S.
Abstract : Objective: To describe the collaborative efforts of a large healthcare institution and its local blood center in reducing preoperative autologous blood donation (PABD). Methods: Through an educational letter-based campaign, we contacted physicians who historically had ordered PABD units. Follow-up educational efforts occurred at departmental and individual meetings. Results: Our educational campaign to reduce PABD achieved complete elimination of PABD orders and the resultant waste of PABD units within 3 years of the start of the program. These changes were sustained for at least 2 subsequent years without the need for additional educational efforts. Conclusion: Targeted educational efforts directed at practitioners of PABD were successful in significantly decreasing the use and waste of PABD at the health care institution we studied and may yield the same results in comparable institutions.